Chainmail Catalyst of Fe3O4@C/CNTO‐Modified Celgard Separator with Low Metal Loading for High‐Performance Lithium–Sulfur Batteries. Issue 13 (18th March 2020) - Du, Jingguang; Ahmed, Waqas; Xu, Jie; Zhang, Mingyuan; Zhang, Zhiliang; Zhang, Xinsheng; Niu, Dongfang
Abstract: Developing the conductive and catalytic composite interface is an efficient way to boost up the conversion of lithium polysulfide (LiPSs) that can effectively resolve the shuttle effect. Besides, achieving the high performance with low metal loading has practical significance for the commercialization of lithium–sulfur (Li−S) batteries. Herein, the chainmail catalyst of Fe3 O4 @C/CNTO was prepared by annealing the iron phthalocyanine (FePc)/oxidized carbon nanotubes (CNTO) precursor in which FePc was used as iron and carbon sources and CNTO was functionalized as oxygen source and catalyst support. The conductive composite catalyst with low metal loading (5.4 wt%) was applied into the coating layer of Celgard separator with duplex functions in trapping and catalyzing intercepted LiPSs for high‐performance Li−S batteries. This work can help us to understand the importance of conductive and catalytic composite interface for promotion of LiPSs conversion and also offer a more feasible synthesis method of electrocatalyst for other energy storage systems. Abstract : The chainmail catalyst of Fe3 O4 @C/CNTO with low metal loading was innovatively constructed and applied into the coating layer of Celgard separator. Benefiting from the conductive and catalytic composite interface, the battery with the Fe3 O4 @C/CNTO‐modified separator delivers a satisfactory specific capacity and excellent stability for Li−S batteries.